Association between high-density lipoprotein cholesterol and 7-autoantibodies: a study on physical examination data from 2018 to 2023 - Zhou, Yang; Sun, Yongbing; Qiao, Qi; Qi, Xin; Lin, Xinbei; Du, Yawei; Liu, Ao; Zhou, Jing; Lv, Xue; Li, Zhonglin; Wu, Xiaoling; Zou, Zhi; et al. (Frontiers in Endocrinology, 2025)
BackgroundLimited research has explored the effect of high-density lipoprotein cholesterol (HDL-C) on lung cancer’s seven autoantibodies (7-AABs). This study investigated the association between serum HDL-C and 7-AABs among 5,574 Chinese adults aged ≥ 18 years from January 2018 to December 2023.MethodsThis cross-sectional study utilized physical examination data from the Department of Health Management at Henan Provincial People’s Hospital. The associations between HDL-C and autoantibodies, such as tumor protein 53(P53), SRY-box containing gene 2 (SOX2), and ATP-dependent RNA helicase 4-5 (GBU4-5), were modeled using a restricted cubic spline logistic regression model.ResultsAfter the adjustment for factors, such as age and body mass index, the binary logistic regression model showed distinct correlations between serum HDL-C levels and autoantibodies, including P53, SOX2, and 7-AABs. Restricted cubic spline logistic regression analysis indicated that the increased level of serum HDL-C was associated with a decreased risk of positive P53 (all participants: HDL-C: 1.227–1.366 mmol/L, PHDL-C=0.028), SOX2 (all participants: HDL-C ≥ 1.227 mmol/L, PHDL-C =0.021; all women: HDL-C ≥ 1.224 mmol/L, PHDL-C=0.037), GBU4-5 (all women: HDL-C ≥ 1.269 mmol/L, PHDL-C=0.039), and 7-AABs (all women: HDL-C ≥ 1.224 mmol/L, PHDL-C=0.015). In women, HDL-C levels between 1.163 and 1.224 mmol/L correlated with an increased risk of positive 7-AABs test results.ConclusionsElevated HDL-C levels exhibited an independent association with a reduced risk of positivity for 7-AABs of lung cancer, especially in the female physical examination population. These findings suggest that high HDL-C levels may play a role in hindering lung cancer development with gender differences. However, further confirmation is still needed in the future.